CLIL implementation in Italian schools: can the long ago employed teacher be trained effectively? The Italian protagonists' voice - Emilia Di Martino; Bruna Di Sabato (Universidad de La Sabana, 2012)
Most Italian upper schools will have to offer at least one subject in a foreign language as part of the national curriculum starting next year. This paper aims to report the results of a survey we carried out between April and June 2011 in order to get the feel of the teachers' expectations, fears and thoughts in the wake of the 'CLIL revolution' in our country. The overall aim of our research is to offer those in charge of the project the possibility to hear the voices of some of the teachers who are being asked to take on a task requiring considerable extra work in a very complex moment for our country, so as to at least attempt to finetune their decisions to actual reality. A partir del próximo año los institutos italianos estarán obligados a impartir una asignatura en un idioma estranjero como parte del curriculo nacional. Objetivo de esta ponencia es informar de los resultados de una encuesta realizada entre abril y junio de 2011 con el fin de sondear las expectativas de los profesores, sus temores y opiniones con vista a la revolución CLIL en Italia. El fin de la investigación es ofrecer a los responsables del proyecto la posibilidad de escuchar las voces de los docentes, a los que se le pedirá una gran mole de trabajo extra en un momento especialmente complejo para el país, con el fin de afinar las modalidades de realización del proyecto mismo con las exigencias de los profesores de instituto y la realidad actual.